Tinjauan Yuridis dalam Pemeriksaan Sidik Jari Dalam Penyidikan Tindak Pidana di Polres Pulau Buru - Lutfi Rumkel (Eastasouth Institute, 2022)
The principle of legal awareness means making every citizen aware to always obey the law, besides that it is also obligatory for the state and its apparatus to enforce and guarantee the validity of legal certainty in Indonesia. With the increasingly advanced and complex era and changes that occur in all directions, indirectly bring up various things in life. Along with the increasing phenomenon of legal problems, there is also an increase in juridical studies that aim to explore various problems from the perspective of existing laws and regulations. In such a situation and condition, it is hoped that the crimes that occurred can be considered more seriously, both for the competent authorities and for the participation of the community, which operationally have not been satisfactorily resolved. The imposition of a crime is not merely as revenge but is aimed at influencing human behavior in accordance with the rules of law.